A Review on Signal in Pharmacovigilance - Rani, Ritu; Chand, Subhash; Singh, Arjun; Kumar, Deovrat; Devi, Meena (Asian Journal of Pharmaceutical Research and Development, 2019)
A safety signal is data or information that may suggest a new causal association, or contribute new information about a known association, between a medicine and an adverse event that justifies further investigation. Signals are generated from several sources such as spontaneous reports, clinical studies and the scientific literature. Signal is a potential medicine safety issues, which are derived from individual case safety reports in vigiBase. Signal detection is a cornerstone of drug development process ensuring drug safety. The early detection of Signals helps to improve patient safety and reduce economic burden due to escalating cost of medications and unwanted adverse effects associated with it. The present study is an initiative to make significant contribution towards health-care system by generating evidence based data to benefit health care professionals, consumers, pharmaceutical companies and regulatory authorities.Signal detection and signal strengthening is the most important aspect in Pharmacovigilance which plays an important role in ensuring that patients receive safe drugs. For detection of adverse drug reactions, clinical trials usually provide limited information as they are conducted under strictly controlled conditions. Some of the adverse drug reaction can be detected only after long term use in larger population and in specific patient groups due to specific concomitant medications or disease.